2022
DOI: 10.1038/s41392-022-00921-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the receptor of oncolytic virus M1 as a therapeutic predictor for multiple solid tumors

Abstract: Over the last decade, oncolytic virus (OV) therapy has shown its promising potential in tumor treatment. The fact that not every patient can benefit from it highlights the importance for defining biomarkers that help predict patients’ responses. As particular self-amplifying biotherapeutics, the anti-tumor effects of OVs are highly dependent on the host factors for viral infection and replication. By using weighted gene co-expression network analysis (WGCNA), we found matrix remodeling associated 8 (MXRA8) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…These factors limit the clinical effectiveness of oncolytic viruses in treating gliomas. [ 222 ] However, the study used neural stem cells (NSCs), which can migrate and spread freely within tumors, to deliver a genetically engineered oncolytic adenovirus (CRAd‐S‐pk7) in a first‐in‐human, open‐label, phase 1, dose‐escalation trial. The phase1 trial has proved the safety and tolerability of NSC‐CRAd‐S‐pk7 injection during surgery in patients, considering that the patients had favorable clinical outcomes (in terms of survival).…”
Section: Cancer Vaccines Based On Tumor Cell Lysatementioning
confidence: 99%
“…These factors limit the clinical effectiveness of oncolytic viruses in treating gliomas. [ 222 ] However, the study used neural stem cells (NSCs), which can migrate and spread freely within tumors, to deliver a genetically engineered oncolytic adenovirus (CRAd‐S‐pk7) in a first‐in‐human, open‐label, phase 1, dose‐escalation trial. The phase1 trial has proved the safety and tolerability of NSC‐CRAd‐S‐pk7 injection during surgery in patients, considering that the patients had favorable clinical outcomes (in terms of survival).…”
Section: Cancer Vaccines Based On Tumor Cell Lysatementioning
confidence: 99%
“…Additionally, Nguyen and colleagues showed that defects in IFN-JAK-STAT pathway as response biomarkers to virotherapy mediated by oncolytic VSV and HSV-1 [ 116 ]. Another recent study identified the receptor of oncolytic alphavirus M1 as a therapeutic predictor for multiple solid tumors [ 117 ]. In summary, we believe that some of these biomarkers are tumor type-specific and/or OV-specific.…”
Section: Oncolytic Viruses and Immunotherapy: Overviewmentioning
confidence: 99%
“…They have the ability to bind with specific receptors and are then internalized by endocytosis. Oncolytic viruses are a group of viruses that can target and bind to specific receptors, which are overly expressed on cancer cells (CD144, CD46, and CD44) [ 57 ]. Cancer cells have weak or deficient interferon (IFN) pathways, which make them more susceptible to infection with oncolytic virus as compared to normal cells.…”
Section: Immunotherapeutic Approaches For the Treatment Of Cervical C...mentioning
confidence: 99%